2001
DOI: 10.1073/pnas.141039198
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular secondary structure rearrangement by the kissing interaction of the Neurospora VS ribozyme

Abstract: Kissing interactions in RNA are formed when bases between two hairpin loops pair. Intra-and intermolecular kissing interactions are important in forming the tertiary or quaternary structure of many RNAs. Self-cleavage of the wild-type Varkud satellite (VS) ribozyme requires a kissing interaction between the hairpin loops of stemloops I and V. In addition, self-cleavage requires a rearrangement of several base pairs at the base of stem I. We show that the kissing interaction is necessary for the secondary struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 45 publications
4
82
0
Order By: Relevance
“…Both studies found that the internal loop comprised two sheared G·A base pairs reminiscent of domain 2 of the hammerhead ribozyme (Pley et al 1994;Scott et al 1995) plus a protonated A + ·C base pair. It has been proposed, on the basis of covariation analysis, that the loop-loop interaction between the substrate and stem V results in a rearrangement of the base pairing in stem Ib of the substrate (Andersen and Collins 2000). This involves the opening of the terminal base pair, the flipping out of C634, and rearrangement of base pairing in stem Ib, such that CCC (635-637) pairs with GGG (623-625).…”
Section: The Structure Of the Substratementioning
confidence: 99%
See 2 more Smart Citations
“…Both studies found that the internal loop comprised two sheared G·A base pairs reminiscent of domain 2 of the hammerhead ribozyme (Pley et al 1994;Scott et al 1995) plus a protonated A + ·C base pair. It has been proposed, on the basis of covariation analysis, that the loop-loop interaction between the substrate and stem V results in a rearrangement of the base pairing in stem Ib of the substrate (Andersen and Collins 2000). This involves the opening of the terminal base pair, the flipping out of C634, and rearrangement of base pairing in stem Ib, such that CCC (635-637) pairs with GGG (623-625).…”
Section: The Structure Of the Substratementioning
confidence: 99%
“…On interacting with stem-loop V, C634 exhibits enhanced reactivity to dimethyl sulphate (Andersen and Collins 2001), but this might result from less than total extrusion of the base from the helix. A number of sequence changes that would be expected to stabilize the altered pattern of base pairing in helix Ib lead to a substantial reduction in cleavage rate (D. Lafontaine, A. McLeod, and D.M.J.…”
Section: The Structure Of the Substratementioning
confidence: 99%
See 1 more Smart Citation
“…25 Examples of more dramatic secondary structure rearrangements that are coupled to tertiary folding transitions are found in the P5abc domain of the Tetrahymena group I ribozyme, 26 the Varkud satellite (VS) ribozyme, 27 and a pseudoknot in the E. coli α operon mRNA. 28 From these examples, it is apparent that the hierarchical levels of RNA structure are intimately linked with each other during the folding process.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Kissing loop complexes have been observed in a variety of RNAs such as tRNAs (Ladner et al 1975), and ribozymes (Lehnert et al 1996, Rastogi et al 1996, Anderson and Collins 2001, and are essential in biological processes including dimerization of retroviral RNAs Tinoco 2000, Reviewed in Paillart et al 1996). A well-known kissing loop complex controls replication of the ColE 1 plasmid in Escherichia coli.…”
Section: Kissing Loop Model Of U4/u6 Di-snrnp Formationmentioning
confidence: 99%